The EU design approach : a global appraisal - Kur, Annette, 1950-; Levin, Marianne, 1942-; Schovsbo, Jens; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
EU legislation for the protection of designs has been described as a 'third way' in contrast to traditional concepts of design protection. This book provides a thorough appraisal of the EU's unique Design Approach; assessing its formation, development and impact over the past decade. The EU Design Approach explores the rationale behind the creation of the Approach; including contributions from two leading EU scholars who were involved in its conception. The contributing authors provide an assessment of the impact that the Design Approach has had on present EU laws, national law systems and adjacent areas of law including copyright and competition law. Chapters also explore more problematic issues associated with the Approach such as: the role of design law in the wider EU framework for the protection of product shapes, and the balancing of interests between rights holders and users. Overall, this book demonstrates that the Design Approach has been largely successful in its aims despite there being some ongoing points of contention. IP scholars will find this book to be a valuable resource of historical and comparative analysis. Practicing IP lawyers and policy makers will also benefit from the inclusion of up-to-date EU and national case law.
Preface / Annette Kur, Marianne Levin and Jens Schovsbo -- 1. The design approach revisited: background and meaning / Annette Kur and Marianne Levin -- 2. The design approach in a design historical perspective / Stina Theilmann-Lock -- 3. The harmonising decisions from Luxembourg / Marianne Levin -- 4. Copyright protection for design creations / Philipp Fabbio -- 5. "Buy me because I'm cool": the "marketing approach" and the overlap be-tween design, trade mark and unfair competition law / Ansgar Ohly -- 6. Design protection for products that are "dictated by function" / Graeme Dinwoodie and Jens Schovsbo -- 7. The design approach and procedural practice - mismatch or smooth transposition? / Annette Kur -- 8. From law in the books to enforcement in court: jurisdiction, applicable law, and sanctions / Annette Kur -- 9. Greeted with a shrug: the impact of the community design system on United States law / Stacy Dogan -- 10. Legal protection of industrial designs in ChinaC / YIN Qile and ZHANG Weijun -- 11. Concluding remarks and perspectives / Annette Kur, Marianne Levin and Jens Schovsbo -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Evropská unie; design; ochranné známky; autorské právo; průmyslové vzory; design; trademarks; copyright; industrial patents; země Evropské unie; European Union countries; e-knihy online; e-books online